Translating Basic Science to Clinical Applications: A Narrative Review of Repurposed Pharmacological Agents in Preclinical Models of Diabetic Neuropathy - Corina Andrei; Oana Cristina Șeremet; Ciprian Pușcașu; Anca Zanfirescu (Biomedicines, 2025)
Diabetic neuropathy (DN) remains a major clinical burden, characterized by progressive sensory dysfunction, pain, and impaired quality of life. Despite the available symptomatic treatments, there is a pressing need for disease-modifying therapies. In recent years, preclinical research has highlighted the potential of repurposed pharmacological agents, originally developed for other indications, to target key mechanisms of DN. This narrative review examines the main pathophysiological pathways involved in DN, including metabolic imbalance, oxidative stress, neuroinflammation, ion channel dysfunction, and mitochondrial impairment. A wide array of repurposed drugs—including antidiabetics (metformin, empagliflozin, gliclazide, semaglutide, and pioglitazone), antihypertensives (amlodipine, telmisartan, aliskiren, and rilmenidine), lipid-lowering agents (atorvastatin and alirocumab), anticonvulsants (topiramate and retigabine), antioxidant and neuroprotective agents (melatonin), and muscarinic receptor antagonists (pirenzepine, oxybutynin, and atropine)—have shown promising results in rodent models, reducing neuropathic pain behaviors and modulating underlying disease mechanisms. By bridging basic mechanistic insights with pharmacological interventions, this review aims to support translational progress toward mechanism-based therapies for DN.